The Multiscale Dynamics of Beat-to-Beat Blood Pressure Fluctuation Links to Functions in Older Adults - Jiang, Xin; Cai, Yurun; Wu, Xiaoyan; Huang, Baofeng; Chen, Yurong; Zhong, Lilian; Gao, Xia; Guo, Yi; Zhou, Junhong (Frontiers in Cardiovascular Medicine, 2022)
Background The blood pressure (BP) is regulated by multiple neurophysiologic elements over multiple temporal scales. The multiscale dynamics of continuous beat-to-beat BP series, which can be characterized by “BP complexity”, may, thus, capture the subtle changes of those elements, and be associated with the level of functional status in older adults. We aimed to characterize the relationships between BP complexity and several important functions in older adults and to understand the underlying factors contributing to BP complexity. Method A total of 400 older adults completed a series of clinical and functional assessments, a finger BP assessment of at least 10 min, and blood sample and vessel function tests. Their hypertensive characteristics, cognitive function, mobility, functional independence, blood composition, arterial stiffness, and endothelial function were assessed. The complexity of systolic (SBP) and diastolic (DBP) BP series was measured using multiscale entropy. Results We observed that lower SBP and DBP complexity was significantly associated with poorer functional independence (β > 0.17, p < 0.005), cognitive function (β > 0.45, p = 0.01), and diminished mobility (β < −0.57, p < 0.003). Greater arterial stiffness (β < −0.48, p = 0.02), decreased endothelial function (β > 0.42, p < 0.03), and excessed level of blood lipids (p < 0.03) were the main contributors to BP complexity. Conclusion Blood pressure complexity is closely associated with the level of multiple functional statuses and cardiovascular health in older adults with and without hypertension, providing novel insights into the physiology underlying BP regulation. The findings suggest that this BP complexity metric would serve as a novel marker to help characterize and manage the functionalities in older adults.